TINJAUAN KELENGKAPAN LAPORAN OPERASI PASIEN RAWAT INAP DI RUMAH SAKIT UMUM SETIA MITRA - Hudiyati Agustini; Ummul Mufidah (APIKES Bhumi Husada Jakarta, 2022)
ABSTRACT The operation report must be filled in completely by the doctor in charge, immediately after the operation is completed. The completeness of the operation report on the status of the patient's medical record is very important as information and documentation of the operation, which can be used by the paying party (insurance) or the court (if a case occurs). The general objective of this study was to determine the completeness of the operating report for inpatients at Setia Mitra Hospital. The research method used is descriptive, with a population of inpatient surgery reports in the period February-August 2020, with a sample of 136 inpatient surgery reports. Based on the results of the research, it is known that Setia Mitra Hospital does not yet have a special SOP regarding filling out operational reports that must be complete. Hospitals only have SOPs in general entitled Planned/Elective Surgical Services, where these SOPs do not follow applicable standards or references. From the results of quantitative analysis calculations, it was found that only 9 statuses (6.6%) had complete operation reports. The component that is filled out 100% is the patient identification, while the least completely filled out is the important notes by 66%. The cause of the incomplete filling of the operation report form is the lack of awareness of human resources about the importance of the operation report, and there is no monitoring and evaluation regarding the completeness of its completion. Keywords: completeness, operation report ABSTRAK Laporan operasi wajib diisi lengkap oleh dokter yang bertanggung jawab segera setelah operasi selesai. Kelengkapan laporan operasi pada status rekam medis pasien sangat penting sebagai informasi dan pendokumentasian operasi, yang dapat digunakan oleh pihak pembayar (asuransi) atau pengadilan (apabila terjadi suatu kasus). Tujuan Umum dari penelitian ini adalah untuk mengetahui kelengkapan laporan operasi pasien rawat inap di RSU Setia Mitra. Metode penelitian yang digunakan adalah deskriptif, dengan populasi laporan operasi pasien rawat inap pada periode bulan Februari−Agustus 2020, dengan sampel sebanyak 136 laporan operasi pasien rawat inap. Berdasarkan hasil penelitian, diketahui bahwa RSU Setia Mitra belum memiliki SPO khusus tentang pengisian laporan operasi yang harus lengkap. Rumah sakit hanya memiliki SPO secara umum yang berjudul Pelayanan Bedah Terencana/Eleketif, di mana SPO ini belum mengikuti standar atau acuan yang berlaku. Dari hasil perhitungan analisis kuantitatif, didapatkan hanya 9 status (6,6%) yang memiliki laporan operasi terisi lengkap. Komponen yang terisi lengkap 100% adalah identifikasi pasien, sedangkan yang paling sedikit terisi lengkap adalah catatan penting sebesar 66%. Penyebab ketidaklengkapan pengisian formulir laporan operasi adalah kurangnya kesadaran sumber daya manusia tentang pentingnya laporan operasi, serta tidak ada monitoring dan evaluasi mengenai kelengkapan pengisiannya. Kata kunci: kelengkapan, laporan operasi